Obstacles in moving to agile software development methods : at a glance. - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abdul Ghani, Abdul Azim; Md. Sultan, Abu Bakar; Nafchi, Mina Ziaei (Science Publications, 2013)
It is only less than a decade that agile SD methods were introduced and got popular steadily. The defined values in these methods and their outcomes have motivated many software producers to use these methods. Since migration from traditional software development methods to agile methods is growing highly, managers of the companies should be aware of problems, hindrances and challenges they may face with during the agile transformation process. This study focused on challenges which companies may face with and it is necessary that managers think about solving them. Classifying them into four main categories; organization and management, people, process and tools are the areas that challenges have been seen in recent studies.